Audible sound treatment of the microalgae Picochlorum oklahomensis for enhancing biomass productivity. (February 2016) - Cai, Weiming; Dunford, Nurhan Turgut; Wang, Ning; Zhu, Songming; He, Huinong
Highlights: Audible sound control had potential to improve algae industrialized production. Sound at 2200 Hz produced significantly higher biomass than other frequencies. Sound at control 2200 Hz increase Picochlorum oklahomensis (PO) biomass by 27.5%. There was no significant difference in the oil content of the PO cultures samples. Abstract: It has been reported in the literature that exposure of microalgae cells to audible sound could promote growth. This study examined the effect of sound waves with the frequency of 1100 Hz, 2200 Hz, and 3300 Hz to stimulate the biomass productivity of an Oklahoma native strain, Picochlorum oklahomensis (PO). The effect of the frequency of sound on biomass mass was measured. This study demonstrated that audible sound treatment of the algae cultures at 2200 Hz was the most effective in terms of biomass production and volumetric oil yield.